2004
DOI: 10.1037/0882-7974.19.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Aging and the Detection of Contingency in Causal Learning.

Abstract: Young and older participants' ability to detect negative, random, and positive response-outcome contingencies was evaluated using both contingency estimation and response rate adaptation tasks. Age differences in contingency estimation were consistently greater for negative than positive contingencies, and these differences, though still present, were smaller when response rate adaptation was used as the measure of contingency learning. Detecting causal contingency apparently becomes more difficult with age, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
46
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 52 publications
5
46
0
Order By: Relevance
“…Of importance, the deficit in processing interactive contextual information does not appear to be a unique feature of schizophrenia, as it has also been observed in healthy older patients (Bayen et al 2000;Braver and Barch 2002). Interestingly, with regard to our current results, impairment in contingency learning has recently been evidenced in older adults (Mutter and Williams 2004). The deficit of processing interactive contextual information seems to reflect a specific dysfunction of the prefrontal cortex that is found in healthy older subjects as well as in schizophrenic and demented patients (Cohen and Servan-Schreiber 1992;Braver and Barch 2002).…”
Section: Discussionsupporting
confidence: 56%
“…Of importance, the deficit in processing interactive contextual information does not appear to be a unique feature of schizophrenia, as it has also been observed in healthy older patients (Bayen et al 2000;Braver and Barch 2002). Interestingly, with regard to our current results, impairment in contingency learning has recently been evidenced in older adults (Mutter and Williams 2004). The deficit of processing interactive contextual information seems to reflect a specific dysfunction of the prefrontal cortex that is found in healthy older subjects as well as in schizophrenic and demented patients (Cohen and Servan-Schreiber 1992;Braver and Barch 2002).…”
Section: Discussionsupporting
confidence: 56%
“…This evidence can be represented as the absolute frequencies of the event state combinations in Cells A – D of a 2 × 2 contingency table (see Figure 1). Studies investigating causal induction through experience often focus on the acquisition of this basic contingency evidence via associative learning processes (e.g., Mutter & Williams, 2004; Shanks & Dickinson, 1987; Wasserman & Castro, 2005), whereas those investigating causal induction via descriptive sources typically focus on differences in how the contingency evidence in these four cells is weighted and the rules that are used to combine this evidence for prediction and judgment (e.g., Levin, Wasserman, & Kao, 1993; Mandel & Lehman, 1998; Schustack & Sternberg, 1981; Shaklee & Mims, 1982; Wasserman, Dorner, & Kao, 1990; White, 2003). …”
mentioning
confidence: 99%
“…In a generative causal contingency, outcome occurrence is more likely in the presence of the cue than in its absence and in a preventative causal contingency, outcome occurrence is more likely in the absence of the cue than in its presence. Research has consistently shown that age differences in causal learning are greater for preventative than generative causal contingencies, suggesting that older adults may have a selective deficit in their ability to acquire causal information about absent cues (Mutter, Haggbloom, Plumlee, & Schirmer, 2006; Mutter & Pliske, 1996; Mutter & Plumlee, 2009; Mutter, DiCaro, & Plumlee, 2009; Mutter & Williams, 2004). If this is the case, age differences should also be observed in other causal scenarios that require learning about absent events.…”
mentioning
confidence: 99%
“…Likewise, age has a detrimental effect on implicit learning tasks such as higher-order sequence learning (e.g., Howard, Howard, Japikse, DiYanni, Thompson, & Somberg, 2004) that involve extracting complex temporal and predictive relationships between co-occurring stimuli. Given the importance of associative processes in causal learning, it seems likely that this extensive age-related associative deficit is also responsible for the changes that have been observed in older adults’ causal learning (Mutter, et al, 2006; Mutter & Pliske, 1996; Mutter & Plumlee, 2009; Mutter, et al, 2009; Mutter & Williams, 2004). …”
mentioning
confidence: 99%
See 1 more Smart Citation